To the freemen of Orange County - Murphey, Archibald D. (Archibald De Bow), 1777-1832 (T. Henderson, printer, 1813)
Pamphlet written by A.D. Murphey to the freemen of Orange County. The document was a review of the various acts and resolutions passed by the North Carolina General Assembly in its November session by one of the representatives of this county. as well as his opinion regarding some.